Pentoxifylline Neuroprotective Effects Are Possibly Related to Its Anti-Inflammatory and TNF-Alpha Inhibitory Properties, in the 6-OHDA Model of Parkinson’s Disease - Kelly Rose Tavares Neves; Hélio Vitoriano Nobre; Luzia Kalyne A. M. Leal; Geanne Matos de Andrade; Gerly Anne de Castro Brito; Glauce Socorro de Barros Viana (Parkinson's Disease)
Pentoxifylline (PTX) is a phosphodiesterase inhibitor with anti-TNF-alpha activity, associated with its anti-inflammatory action. Considering Parkinson’s disease (PD) as a neuroinflammatory disorder, the objectives were to evaluate PTX neuroprotective properties, in a model of PD. Male Wistar rats, divided into sham-operated (SO), untreated 6-OHDA, and 6-OHDA treated with PTX (10, 25, and 50 mg/kg) groups, received a unilateral 6-OHDA injection, except the SO group administered with saline. Treatments started 24 h after surgery and continued for 15 days when the animals were submitted to apomorphine-induced rotations, open field, and forced swimming tests. At the next day, they were euthanized and their striata processed for neurochemical (DA and DOPAC determinations), histological, and immunohistochemical (Fluoro-Jade, TH, DAT, OX-42, TNF-alpha, COX-2, and iNOS) studies. PTX reversed the behavioral changes observed in the untreated 6-OHDA animals. Furthermore, PTX partially reversed the decrease in DA contents and improved neuronal viability. In addition, decreases in immunostaining for TH and dopamine transporter (DAT) were reversed. The untreated 6-OHDA group showed intense OX-42, TNF-alpha, COX-2, and iNOS immunoreactivities, which were attenuated by PTX. In conclusion, we demonstrated a neuroprotective effect of PTX, possibly related to its anti-inflammatory and antioxidant actions, indicating its potential as an adjunct treatment for PD.